A note on Philippine financial openness - Tan, Jose Antonio, III (Philippine Review of Economics and Business (formerly The Philippine Review of Business and Economics), 1998)
In 1991, the Philippines launched a series of foreign exchange reforms which partially openned the capital account. These set of reforms, if completed, will result in the financial integration of the economy with the global financial markets, thus, would complete the sequence of economic liberalization and integration. This study examines the degree of financial integration of the Philippines with the international economy. In particular, two questions are to be answered. First, how financially integrated is the Philippines with the rest of the world? And, second, how has foreign exchange liberalization contributed to Philippine financial openness? Philippine financial openness is examined using the gross capital flows ratio, the Feldstein-Horioka regressions, and variations of tests based on uncovered interest parity. While the results confirm the substantial increase in gross capital flows, evidence using investment-saving correlation and arbitrage tests suggest that the degree of financial openness is still low. The empirical evidence also suggests that capital account liberalization has not contributed much to financial integration.